2016
DOI: 10.1002/anie.201511609
|View full text |Cite
|
Sign up to set email alerts
|

Weak and Transient Protein Interactions Determined by Solid‐State NMR

Abstract: Despite their roles in controlling many cellular processes, weak and transient interactions between large structured macromolecules and disordered protein segments cannot currently be characterized at atomic resolution by X-ray crystallography or solution NMR. Solid-state NMR does not suffer from the molecular size limitations affecting solution NMR, and it can be applied to molecules in different aggregation states, including non-crystalline precipitates and sediments. A solid-state NMR approach based on high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…We proposed that this could result from the acidic tip of one SSB tetramer interacting with an unoccupied ssDNA binding site of a neighboring tetramer [27]. Such interactions have been demonstrated at high SSB concentrations [33]. However, this type of interaction is precluded in the (SSB) 65 mode since all ssDNA binding sites are occupied by DNA.…”
Section: Discussionmentioning
confidence: 99%
“…We proposed that this could result from the acidic tip of one SSB tetramer interacting with an unoccupied ssDNA binding site of a neighboring tetramer [27]. Such interactions have been demonstrated at high SSB concentrations [33]. However, this type of interaction is precluded in the (SSB) 65 mode since all ssDNA binding sites are occupied by DNA.…”
Section: Discussionmentioning
confidence: 99%
“…However, all building blocks of the pulse sequences have been shown to perform also on non-crystalline formulations. 18 , 31 33 Given the difficulty of obtaining good-diffracting crystals for large RNA–protein complexes, we anticipate that these results will strengthen the role of MAS NMR in RNA structural biology, and more generally provide momentum in the atomic-level description of structure and dynamics of RNA.…”
mentioning
confidence: 85%
“…In a recent study, Dannatt, et al [146], showed that E. Coli single-stranded DNA binding protein readily forms hydrogels in vitro . Using ssNMR methods to measure CSPs and 15 N R 1ρ values, showed that the C-terminal acidic motif transiently interacts with the DNA binding groove, thus rationalizing the observed hydrogelation and providing a mechanism for the observed auto-inhibition [146].…”
Section: Structural Characterization Of Molecular Network Within Memmentioning
confidence: 99%